The Miriam Dell Award - Editors (New Zealand Science Review, 2014)
​In 2013, the Association for Women in the Sciences (AWIS) launched the Miriam Dell Award for Excellence in Science Mentoring, a biennial prize awarded to someone who demonstrates outstanding mentoring efforts to retain females in science, mathematics or technology.The recipient of the Miriam Dell Award may be related to any part of the science system, for example teachers at primary or secondary schools, lecturers or supervisors in tertiary education, or in the science workplace. Mentees may also be at any stage in the science system – from school age to the science workforce